Koordinasi Sinyal antar Simpang untuk Mengurangi Kemacetan di Jalan P.B. Sudirman Denpasar dengan Menggunakan Software TRANSYT 15 - Decky Cipta Indrashwara; P. Adi Yasa (Jurnal Manajemen Teknologi & Teknik Sipil, 2022)
On Jalan P.B Sudirman there are 3 intersections. The conditions of the three intersections are currently uncoordinated, as a result, vehicles that have just passed the Puputan Renon Intersection have to stop waiting for the green phase to return at the FE Unud Intersection and the same thing also happens at the Waturenggong Intersection. As a result, long queues, delays, and the number of stops, especially during peak hours, are unavoidable. For this reason, it is necessary to carry out an analysis of proper coordination between intersections, to reduce traffic jams at the three intersections. The purpose of this study is to analyze the signal coordination between the three intersections using TRANSYT 15 software. The research was conducted by analyzing primary data and secondary data with MKJI to obtain values of Capacity, Queue Length, Delay, Saturation Degree, and Level of Service for existing conditions, then analyze the existing signal settings for the three intersections using the Time-Distance Diagram method. Signal coordination analysis was performed using TRANSYT 15 and the results from the software were compared with the existing conditions. The result show that the arm Capacity has increased from the existing condition at The Puputan Renon, FE Unud, and Waturenggong Intersections, they were 36.93%, 21.43%, and 70.16%, Degrees of Saturation were decreased to 23%, 29.14%, and 41.53%, and the Number Stop Value were decreased to 94.08%, 73.21%, and 83.74%. From the results of this study, it can be applied to reduce congestion that occurs along P.B. Sudirman Street.